Data Analytics Maturity Model for Digital Product Innovation in Firm: An Overview - Alamsyah, Noor; Thanasopon, Bundit; Jamsri, Pornsuree (My University, 2025)
This paper aims to report the results of the review, map the characteristics, and conduct a comparative analysis of the selected data analytics maturity models that are commonly implemented in firms engaged in digital product innovation. The maturity models examined include TDWI, Hortonworks, Gartner, and DELTA Plus, which represent some of the most recognized framework guiding organizations in assessing and improving their data analytics capabilities. Characteristics and comparative analysis were developed based on investigative literature reviews, referring to official reports from institutions that developed the model and publications that discussed the model. Each maturity model is explained concisely and comprehensively, highlighting the structure, dimensions, and progression criteria that define each maturity level and stage. The comparison indicates that although these models outline well-defined conceptual stages of analytics maturity, most provide limited methodological guidance for assessing firms or determining their placement within a spesific maturity level. In the future, it is expected there will be an increase in the availability of maturity models that are more adaptive and personalized for various business sectors. This paper contributes to present a fairly intensive comparative analysis and characterization of data analytics maturity models that are widely recognized and frequently applied in supporting digital product development within firms. In addition to that, this paper provides a cost model. The model is evaluated using Genetic Algorithm (GA) and Simulated Annealing (SA).
Keywords: data analytics; digital product innovation; maturity assessment; maturity models